PENERAPAN SISTEM INFORMASI CREDIT UNION INDONESIA (SICUNDO) PADA KOPERASI KREDIT SEHATI KARANGSARI LAMPUNG TENGAH - Yohanes P Kumagaya (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2017)
The purpose of this study was to investigate the application of Information Systems CreditUnion Indonesia (SICUNDO) at the Credit Union Sehati. Kopdit Sehati need a better system to help theperformance of cooperatives in order to produce the financial statements are more efficient andaccurate. The above problems need to be dealt with using a better system in terms of technology,namely the credit union system information Indonesia (SICUNDO). The method used to determine theapplication Kopdit Sehati SICUNDO on the analysis of qualitative and quantitative analysis. Qualitativeanalysis comparing manual systems and information systems of the credit union Indonesia (SICUNDO)imposed by Kopdit Sehati. Quantitative analysis is comparing the lending and financial statementsbefore and after wearing SICUNDO.